IN HISTORY’S SHADOW: CHILD WELFARE DISCOURSES REGARDING INDIGENOUS COMMUNITIES IN THE CANADIAN SOCIAL WORK JOURNAL - Schmid, Jeanette; Morgenshtern, Marina (International Journal of Child, Youth and Family Studies, 2022)
This article reviews all items in the Canadian Social Work journal over its almost 90-year history that relate to child welfare practice in an Indigenous context. We review the journal contents as a way of understanding the profession’s voice, noting that a journal’s discursive practice reflects disciplinary discourse and that this journal positioned itself as a platform for social work debates. Our analysis contributes also to the truth-telling and accountability of social workers. While around 10% of the 1500 journal articles focused on child welfare practice, only 9 of these 152 articles addressed child welfare practice with Indigenous children and families. Our discourse analysis highlights that there was contemporaneous silence regarding social work complicity in the residential schools movement, the Sixties Scoop, and the current Millennium Scoop. In the 1980s, sustained critique around the role of social work in perpetuating colonization began to emerge. The journal, though, left child protection discourse unexamined and thus overlooked its role in maintaining dominant Canadian child welfare practice. We suggest that White supremacy and settler colonial discourses support the dominance of the child protection discourse, and that part of decolonizing child welfare practice relates to revealing and resisting these discourses and generating alternative decolonized discourses.